Сутність та види точок контакту бренду зі споживачами - Бойко, Ірина Анатоліївна; Скригун, Наталія Петрівна; Навроцький, Назарій Андрійович (My University, 2024)
У статті обґрунтовано необхідність уточнення сутності поняття «точка контакту з брендом» та узагальнення видів точок контакту бренду зі споживачами. Показано, що взаємодія споживача з брендом відбувається в багатьох точках контакту, які важливі насамперед тим, що впливають на досвід клієнта, його поведінку, продажі, прибуток компанії. Розглянуто існуючі підходи до трактування сутності поняття «точки контакту з брендом» через відображення різноманітних взаємодій між споживачами та компанією (брендом), що охоплюють будь-які канали та медіа, через які споживачі сприймають бренд чи продукт та можуть бути ініційовані як компанією, так і споживачами. Визначено, що ідентифікація та оцінювання точок контакту є важливою функцією підприємства задля покращення клієнтського досвіду. Уточнено та систематизовано види точок контакту бренду зі споживачами, що дозволяє підприємству вибудовувати міцні і довготривалі зв'язки зі споживачами та забезпечувати конкурентні переваги на ринку

The necessity of clarification the essence of concept “touchpoints with a brand” and generalization of different types of brand’s touchpoints with consumers is considered in the article. It is shown that co-operating of consumer with a brand takes place in many points of contact that is important first to those that influence on client’s experience, his/ her behavior, sales, and company profit. They are not limited by product quality or relation of salesperson and can be both physical and to take place personally. The existent approaches to the interpretation of the essence of concept “touchpoints with a brand” through the reflection of various cooperation between consumers and company (by a brand), that embrace any channels and medias, through that consumers perceive a brand or product and can be initiated by both a company and consumers are considered. Certainly, that authentication and evaluation of touchpoints are the important function of the enterprise for improvement of clients’ experience. To determine the touchpoints that belong to the brand as places of co-operating with a client during the service using, that is worked out and managed by a firm and under its control, and touchpoints that belong to the partners as co-operating with a client during its experience, that is developed, managed or controlled by a firm and by one or a few partners is offered. Touchpoints that belong to the client – all moments of cooperation of client with this company, that take place through different channels and medias that is felt or used by a client; they characterize the client’s actions, that are part of general client experience, but a firm, its partners or other persons, does not influence and does not control is found out. Social (external) touchpoints surround consumers during their client experience and play an important role is shown in the article. The types of brand’s touchpoints are specified and systematized with consumers, that allows the enterprise to line up strong and of long term connections with consumers and provide competitive edges at the market. Distinguished and grouped brand’s touchpoints of contact with a consumer give companies basis for understanding of potential levers of influence on client experience
Keywords: кафедра маркетингу; бренд; brand; споживач; consumer; точка контакту; touchpoints; канали комунікацій; communication channels; соціальні мережі; social networks